2000
DOI: 10.1007/pl00010707
|View full text |Cite
|
Sign up to set email alerts
|

Recommended care for young people (15–19 years) after suicide attempts in certain European countries

Abstract: Data on recommended care for young people aged 15±19 years after attempted suicide from nine European research centres during the period 1989±1992 were analysed in terms of gender, history of previous suicide attempt and methods used. Altogether 438 suicide attempts made by 353 boys and 1,102 suicide attempts made by 941 girls were included. Analyses of the total data from all centres showed that young people with a history of previous suicide attempt and those using violent methods had signi®-cantly higher ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
2
17
1
3
Order By: Relevance
“…A somewhat lower rate of psychiatric aftercare following general hospital presentation for self-harm has previously been found in adolescents in England compared to other countries in Europe [41]. The low rate of psychiatric hospital admission is particularly notable, but in accord with previous findings from the UK [6].…”
Section: Discussionsupporting
confidence: 83%
“…A somewhat lower rate of psychiatric aftercare following general hospital presentation for self-harm has previously been found in adolescents in England compared to other countries in Europe [41]. The low rate of psychiatric hospital admission is particularly notable, but in accord with previous findings from the UK [6].…”
Section: Discussionsupporting
confidence: 83%
“…Providing patients with mental health follow up after a suicide attempt can reduce the rate of future attempts (Mann et al, 2008), however, the scant research that has been done shows that patients are not receiving appropriate follow up care. Hulten et al (2000) reported that in nine European countries most adolescents did not receive follow up recommendations after an emergency room visit for suicide attempts if the attempt was a first attempt and if the chosen method of attempted suicide was self-poisoning. Adolescents who chose more violent methods, such as a firearm, hanging or jumping and had previously attempted suicide were more likely to receive follow up referrals to mental health providers (Hulten et al, 2000).…”
Section: Emergency Departments and Suicidal Patientsmentioning
confidence: 98%
“…Hulten et al (2000) reported that in nine European countries most adolescents did not receive follow up recommendations after an emergency room visit for suicide attempts if the attempt was a first attempt and if the chosen method of attempted suicide was self-poisoning. Adolescents who chose more violent methods, such as a firearm, hanging or jumping and had previously attempted suicide were more likely to receive follow up referrals to mental health providers (Hulten et al, 2000). Baraff et al (2006) also found that care for suicidal patients in the ED is inconsistent.…”
Section: Emergency Departments and Suicidal Patientsmentioning
confidence: 98%
“…Therefore, it is important to provide adequate aftercare, directly following a suicide attempt, in order to reduce the risk of repetition. The types of aftercare include inpatient or outpatient psychiatric care with a psychiatrist, pscyhologist or supportive contact for both the individual and non-psychologic care, for example, with a school counsellor, social wellfare officer or a general practitioner (15).…”
Section: Discussionmentioning
confidence: 99%